The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/1592596
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Its Help Seeking Behaviors: A Systematic Review and Meta-Analysis of Community Survey in Ethiopia

Abstract: Background Depression is one of the most common mental illnesses affecting around 322 million individual in the world. Although the prevalence of depression is high and its treatment is effective, little is known about its pooled prevalence and help seeking behaviors in the community settings of Ethiopia. Thus, this study aimed to determine the pooled prevalence of depression and its help seeking behaviors in Ethiopia. Methods A systematic literature search in the databases of Pub-Med, Cochrane, and Google Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 74 publications
0
25
5
2
Order By: Relevance
“…Our finding is higher than what has been reported in the general population of Ethiopia. In a meta-analysis of Ethiopian studies the pooled prevalence of the help-seeking intention of people with depression in Ethiopia is 42% [35] which is much lower than the current finding. The possible explanations for the difference could be difference in mental health literacy, study population and data collection instruments being used.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Our finding is higher than what has been reported in the general population of Ethiopia. In a meta-analysis of Ethiopian studies the pooled prevalence of the help-seeking intention of people with depression in Ethiopia is 42% [35] which is much lower than the current finding. The possible explanations for the difference could be difference in mental health literacy, study population and data collection instruments being used.…”
Section: Discussioncontrasting
confidence: 79%
“…However, only few people receive professional mental health service. For instance, a meta-analysis reported that the pooled prevalence of formal mental health help-seeking behaviors and intention of people with depression is 38% and 48%, respectively [35]. In Ethiopia, most people with mental illness first contact non-professional care providers such as religious leaders and herbalists [36].…”
mentioning
confidence: 99%
“…Previous literatures showed more than one in ve of the community residents (20.5%) had depression in Ethiopia (21). We examined communities' preference to seek help for depression by presenting them a vignette depicting an individual experiencing a major depressive disorder and asking them to report their preferences to seek help from formal and/ informal sources if they were having a similar situation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it increases the burden of other chronic medical illnesses such as HIV/AIDS, cardiac failure, diabetes mellitus,tuberculosis and surgical illness (9,10). Its' impact on the cause of life threating illnesses is unbearable in low income countries including Ethiopia (11,12) with the estimated magnitude ranging from 2.4% to 60% (13)(14)(15)(16)(17).The other trajectory consequence of depression is suicide (8,18,19) and substance use (20,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation